Dietary l-Arginine Supplementation Protects Weanling Pigs from Deoxynivalenol-Induced Toxicity - Li Wu; Peng Liao; Liuqin He; Zemeng Feng; Wenkai Ren; Jie Yin; Jielin Duan; Tiejun Li; Yulong Yin (Toxins, 2015)
This study was conducted to determine the positive effects of dietary supplementation with l-arginine (Arg) on piglets fed a deoxynivalenol (DON)-contaminated diet. A total of eighteen, 28-day-old healthy weanling pigs were randomly assigned into one of three groups: uncontaminated basal diet (control group), 6 mg/kg DON-contaminated diet (DON group) and 6 mg/kg DON + 1% l-arginine (DON + ARG group). After 21 days of Arg supplementation, piglets in the DON and DON + ARG groups were challenged by feeding 6 mg/kg DON-contaminated diet for seven days. The results showed that DON resulted in damage to piglets. However, clinical parameters, including jejunal morphology, amino acid concentrations in the serum, jejunum and ileum, were improved by Arg (p < 0.05). Furthermore, the mRNA levels for sodium-glucose transporter-1 (SGLT-1), glucose transporter type-2 (GLUT-2) and y+l-type amino acid transporter-1 (y+LAT-1) were downregulated in the DON group, but the values were increased in the DON + ARG group (p < 0.05). Collectively, these results indicate that dietary supplementation with Arg exerts a protective role in pigs fed DON-contaminated diets.